2021
DOI: 10.1055/a-1496-8114
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Different Antithrombotic Strategies after Transcatheter Aortic Valve Implantation: A Network Meta-Analysis

Abstract: Background The optimal pharmacological therapy after transcatheter aortic valve implantation (TAVI) remains uncertain. We compared efficacy and safety of various antiplatelet and anticoagulant approaches after TAVI by a network meta-analysis. Methods A total of 14 studies (both observational and randomized) were considered, with 24,119 patients included. Primary safety endpoint was the incidence of any bleeding complications during follow-up. Secondary safety endpoint was major bleeding. Efficacy end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
4
0
3
Order By: Relevance
“…Additionally, a recent meta-analysis of 4 studies including 2032 patients post-TAVR with concomitant AF has shown that major and life-threatening bleeding rates are lower in patients on an OAC regimen compared to OAC + antiplatelet regimens, while the risk of stroke and mortality do not differ between the groups. 96 Similar results were demonstrated in a meta-analysis by Navarese et al., 64 showing that OAC therapy alone reduced bleeding rates compared to OAC + SAPT regimens, without affecting stroke rates, in patients requiring long-term anticoagulation. On the contrary, another study of the PARTNER 2 trial by Kosmidou et al.…”
Section: Antithrombotic Regimen After Tavrsupporting
confidence: 67%
See 2 more Smart Citations
“…Additionally, a recent meta-analysis of 4 studies including 2032 patients post-TAVR with concomitant AF has shown that major and life-threatening bleeding rates are lower in patients on an OAC regimen compared to OAC + antiplatelet regimens, while the risk of stroke and mortality do not differ between the groups. 96 Similar results were demonstrated in a meta-analysis by Navarese et al., 64 showing that OAC therapy alone reduced bleeding rates compared to OAC + SAPT regimens, without affecting stroke rates, in patients requiring long-term anticoagulation. On the contrary, another study of the PARTNER 2 trial by Kosmidou et al.…”
Section: Antithrombotic Regimen After Tavrsupporting
confidence: 67%
“…62 Other recent studies and updated meta-analyses largely agree with the findings that post-TAVR DAPT therapy increases the risk of bleeding events without reducing the rates of thromboembolism and mortality compared to SAPT. [63][64][65][66] Even though these results are in agreement, larger studies with a longer mean follow-up time are required to adequately assess these end points more effectively.…”
Section: Antiplatelet Therapiesmentioning
confidence: 83%
See 1 more Smart Citation
“…In fact, among patients with mechanical heart valves, the occurrence of both bleeding and ischemic events was higher in those receiving dabigatran versus VKAs, regardless of concomitant AF [17]. Moreover, in randomized studies on patients with AF the incidence of hemorrhagic complications, also including early post-procedural events, was similar with NOACs and VKAs after percutaneous ablation procedures [18], transcatheter aortic valve intervention [19], or cardioversion [20]. Finally, in a study-level meta-analysis on AF patients undergoing non-cardiac surgery, VKAs were as effective and safe as NOACs [21].…”
Section: Discussionmentioning
confidence: 99%
“…A large-scale network meta-analysis on more than 24,000 patients from 14 studies revealed that single antiplatelet therapy lowered the risk of bleeding with no changes in stroke, myocardial infarction, or cardiovascular death when compared with dual antiplatelet therapy. 63 In addition, oral anticoagulation treatment seemed beneficial for patients with an indication for long-term anticoagulation.…”
Section: Single Versus Dual Antiplatelet Therapy In Cardiac Surgery A...mentioning
confidence: 99%